Assessing technologies for information sharing in international research teams: Developing an intercultural heuristic evaluation tool. Issue 1 (24th October 2017) - Ward, Wesley S.; Given, Lisa M.
ABSTRACT: Collaborative research teams working in developing countries rely on information and computer technologies (ICTs), both hardware and software, to overcome barriers to information sharing including, language, distance, time, economic development and politics. However, studies have shown impediments to information sharing between team members from different cultures, nations and institutions. This paper reports on a study in which a model was developed to highlight the most important barriers for communication and information sharing in international research teams, which was the basis for the development of a heuristic evaluation tool. The communication model was created using the results of 30 semi‐structured interviews with agricultural scientists working in international research teams based in Australia and Lao People's Democratic Republic. Interview data outline a number of barriers and facilitators for team communication, which informed the development of eight intercultural heuristics. These were combined with Jakob Nielsen's general usability heuristics to form the intercultural heuristic evaluation tool, or I‐CHET. The tool was then tested in a pilot study to assess the utility and usability of two ICTs used by international research teams: email and Skype. The initial assessment using I‐CHET showed that while email theoretically lacked the richness of cues seen in Skype, email better complied with the needs of international research groups for sharing information and communicating in multicultural teams dispersed over language, cultural and geographic divides.